2019
DOI: 10.1159/000492820
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Ageing Population on the Burden of Stroke: The Dijon Stroke Registry

Abstract: Background: We aimed to evaluate the impact of the ageing population on temporal trends in burden of stroke and to provide projections for the coming years. Methods: Stroke cases (ischemic strokes, spontaneous intracerebral hemorrhages, or undetermined strokes) were prospectively identified between 1987 and 2015 in Dijon, France, using a population-based registry. Age-standardized incidence rates of first-ever and recurrent stroke were calculated, and their temporal trends were assessed using age- and sex-adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 17 publications
(20 reference statements)
2
66
0
6
Order By: Relevance
“…This finding suggests that the increase in stroke risk with age in our main analysis of PFO cohorts is not simply due to the increase in the background vascular risk burden with age. 21 The choice of a different age threshold of 65 years (as opposed to 60 years used in PFO trials) for our analysis of risk for PFO vs no PFO was related to the age thresholds reported in the studies included in the analysis. 9 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that the increase in stroke risk with age in our main analysis of PFO cohorts is not simply due to the increase in the background vascular risk burden with age. 21 The choice of a different age threshold of 65 years (as opposed to 60 years used in PFO trials) for our analysis of risk for PFO vs no PFO was related to the age thresholds reported in the studies included in the analysis. 9 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…We estimated the projected sample size for trials of PFO closure vs medical treatment only after cryptogenic TIA/stroke in patients aged 60 years or older with 80% power to detect either a 66% risk reduction for the interventional closure arm, which was expected on the basis of trials predominantly on antiplatelet treatment in the younger population, or a more conservative 33% reduction to allow for the higher background risk of stroke in the older population or a comparison with anticoagulation. 21 …”
Section: Methodsmentioning
confidence: 99%
“…266 A study from the Dijon Stroke Registry reported an increase in recurrent strokes due to improved stroke care and more stroke survivors with longer survival, which is relevant with populations ageing in industrialized countries. 270 On the other hand, a Swedish study found a reduction in incidence of both first and recurrent stroke, concluding that there were no indications of an increased stroke burden. 269 More studies are needed on this matter.…”
Section: Long-term Recurrent Ischemic Stroke or Tiamentioning
confidence: 98%
“…Still, studies on stroke recurrence trends differ on whether recurrence rates are declining in industrialized countries. 168,265,266 Some studies from selected populations indicate a decline in recurrence rates, 175,[267][268][269] other have reported an increase in incidence, 263,270 but a recent metaanalysis estimated the annual recurrent stroke risk to be ≈4.26% without any observable decline over time. 266 A study from the Dijon Stroke Registry reported an increase in recurrent strokes due to improved stroke care and more stroke survivors with longer survival, which is relevant with populations ageing in industrialized countries.…”
Section: Long-term Recurrent Ischemic Stroke or Tiamentioning
confidence: 99%
“…As the population ages and the risk of thromboembolic disease increases, the number of patients who require antithrombotic therapy also increases. 15,16 Moreover, various antithrombotic medications, including aspirin, nonsteroidal anti-inflammatory drugs, adenosine diphosphate receptor/P2Y 12 inhibitors, glycoprotein IIb/IIIa inhibitors, prostacyclin, thromboxane inhibitors, phosphodiesterase inhibitors, vitamin K antagonists, heparin, and non-vitamin K-dependent oral anticoagulants (NOAC), are available. 17 To cope with these changes, many clinical studies are being conducted and sev-eral global guidelines are being updated.…”
Section: Introductionmentioning
confidence: 99%